Nucleus Accumbens Modulation in Reward and Aversion - Klawonn, Anna M; Malenka, Robert C (Cold Spring Harbor Symposia on Quantitative Biology, 2018)
The nucleus accumbens (NAc) is a key node of the brain's circuitry that is responsible for translating motivation into action. It has been implicated in playing critical roles in virtually all forms of adaptive and pathological motivated behaviors. It is subject to modulation by a broad array of inputs that influence NAc activity in complex ways that are still poorly understood. Here, we briefly review current knowledge about the behavioral consequences of NAc modulation, focusing on recent studies that use novel techniques developed and implemented over the last decade.